Building An Android-Based Application For Teenage Women's Reproductive Health Education - Kusumaningrum, Hesti; Herawati, Dewi Marhaeni; Susiarno, Hadi (JKM (Jurnal Kebidanan Malahayati), 2024)
Background: Improper nutritional intake during adolescence can cause health problems, such as: impaired physical growth, increased risk of iron deficiency (Iron Deficiency Anemia), decreased intellectual capacity, impaired bone health, impaired sexual organ function, impaired concentration and performance at school, eating disorders and obesity, as well as malnutrition, but teenagers' knowledge about nutrition is very limited. Teenagers easily adapt to digital literacy. Providing digital interventions can have a positive impact on various aspects of health so that efforts to empower teenagers through increasing health promotion and early detection of adolescent health problems digitally are growing rapidly. Aim: The aim of this research is to explore the needs of young women for Android-based nutritional and reproductive health educational applications. Method: The qualitative research method is in-depth interviews via the Zoom application, WhatsApp video call, or WhatsApp voice call. Result: The results of qualitative research show that young women prefer educational media that is easy and fast in providing health information so that educational efforts via smartphones, namely Android-based applications, are an effective solution in providing precise and accurate information about nutritional intake and reproductive health. Keywords: Reproductive Health, Young Women, Application